Identifying the presence of gastric cancer risk factors in Campbelltown residents aged 50 to 80 years old, and determining the potential for risk factor modification following education - Aljumah, Mohammad I.; Coric, Daniel; Sun, David; Akhtar, Ridha; Arasaratnam, Lavanya (International Journal Of Community Medicine And Public Health, 2018)
Background: Gastric cancer remains an important cause of mortality in Australia, with modifiable risk factors playing a prominent preventable part in its development. The primary objective of this study is to identify gastric cancer risk factors in people living in Campbelltown area aged 50-80 years old, and to determine the potential for risk factor modification following education. Methods: This is a post-test only intervention study where data was collected through face to face interviews. The survey consisted of questions gathering general information on demographics and identifying the presence of gastric cancer risk factors. An educational sheet was then provided to educate participants on the risk factors and epidemiological data for gastric cancer. Participants were then asked questions to determine their willingness to modify their risk factors, based on what they had learnt from the educational pamphlet. The data collected was analysed using Statistical Package for the Social Sciences (SPSS) software. Results: A total of 137 participants were included in the study. The results show participants were likely or highly likely to modify 45% of their gastric cancer risk factors following education. We also found that women were more likely to reduce their intake of pickled and processed food, and that participants in the younger age group were more likely to reduce salted food intake. Conclusions: Our study indicates that education may influence and may have a varying impact on the willingness of participants to modify gastric cancer risk factors. Furthermore, variables such as age and gender have impact on the willingness to modify certain risk factors.